Cytarabine induces cachexia with lipid malabsorption via zippering the junctions of lacteal in murine small intestine - Mi-Rae Park; Hye-Jin Lee; Hye-Min Jang; Nam Hoon Kim; Jun-Seok Lee; Yong Taek Jeong; Inho Kim; Sang-Hyun Choi; Kwan Sik Seo; Dong-Hoon Kim (Journal of Lipid Research, 2023)
Chemotherapy-induced cachexia causes severe metabolic abnormalities independently of cancer and reduces the therapeutic efficacy of chemotherapy. The underlying mechanism of chemotherapy-induced cachexia remains unclear. Here we investigated the cytarabine (CYT)-induced alteration in energy balance and its underlying mechanisms in mice. We compared energy balance-associated parameters among the three groups of mice: CON, CYT, and PF (pair-fed mice with the CYT group) that were intravenously administered vehicle or CYT. Weight gain, fat mass, skeletal muscle mass, grip strength, and nocturnal energy expenditure were significantly lowered in the CYT group than in the CON and PF groups. The CYT group demonstrated less energy intake than the CON group and higher respiratory quotient than the PF group, indicating that CYT induced cachexia independently from the anorexia-induced weight loss. Serum triglyceride was significantly lower in the CYT group than in the CON group, whereas the intestinal mucosal triglyceride levels and the lipid content within the small intestine enterocyte were higher after lipid loading in the CYT group than in the CON and PF groups, suggesting that CYT inhibited lipid uptake in the intestine. This was not associated with obvious intestinal damage. The CYT group showed increased zipper-like junctions of lymphatic endothelial vessel in duodenal villi compared to that in the CON and CYT groups, suggesting their imperative role in the CYT-induced inhibition of lipid uptake. CYT worsens cachexia independently of anorexia by inhibiting the intestinal lipid uptake, via the increased zipper-like junctions of lymphatic endothelial vessel.